2018
DOI: 10.1080/09540121.2018.1441971
|View full text |Cite
|
Sign up to set email alerts
|

The experience and management of HIV stigma among HIV-negative adults in heterosexual serodiscordant relationships in New York City

Abstract: Despite treatment advances that have improved the health and life expectancy of HIV-positive people and contribute to the prevention of HIV transmission, HIV stigma is still frequently experienced by HIV-infected individuals and those close to them. This study investigated the types of HIV-related stigma experienced by HIV-negative adults in serodiscordant heterosexual relationships when their partner's HIV-positive status was revealed to family and friends and their strategies to manage such stigma. In-depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
2
8
0
8
Order By: Relevance
“…To our knowledge, this is the first study examining the interaction between couples' we-ness and stigma experience in HIV serodiscordant couples. Our findings are consistent with the experience of PLWHA and seronegative spouses reported in previous qualitative studies (Rispel, Cloete, & Metcalf, 2015;Siegel et al, 2018). For instance, a concern of bringing stigma to spouses led to enormous distress and even suicidal attempts in PLWHA who were injection drug users (Salter et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…To our knowledge, this is the first study examining the interaction between couples' we-ness and stigma experience in HIV serodiscordant couples. Our findings are consistent with the experience of PLWHA and seronegative spouses reported in previous qualitative studies (Rispel, Cloete, & Metcalf, 2015;Siegel et al, 2018). For instance, a concern of bringing stigma to spouses led to enormous distress and even suicidal attempts in PLWHA who were injection drug users (Salter et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, PLWHA is particularly distressful about bringing disgrace to the couple, and the seronegative spouses feel devalued because "we have HIV", even if they are not infected. Previous qualitative studies showed that such process brought additional shame, guilt and isolation to discordant couples, exacerbating the negative consequences of stigma (Li et al, 2008;Siegel et al, 2018). We-ness entailed in couple identity may further facilitate the transmission of distress within the couple (Larson & Almeida, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquellos que revelaron el estado serológico informaron de actitudes estigmatizantes como distanciamiento, desprecio, violación de la privacidad y acusaciones por parte de su pareja y de su círculo social más cercano. Ante esto, se mostraron diferentes formas de gestionar la enfermedad dentro de la pareja, tales como la ruptura, la búsqueda de apoyo social externo y la educación a familiares y amigos sobre la enfermedad (Siegel et al, 2018).…”
Section: Resultsunclassified
“…1) pré-análise; 2) exploração do material e 3) o tratamento dos resultados e interpretação 12,13 . 16 .…”
Section: Introductionunclassified